PSYCHOANALYSIS WITH ADOLESCENTS AND CHILDREN learning to surf. - Brady, Mary T., 1959- ([S.l.] : ROUTLEDGE, 2024)
"In Analysing Adolescents and Children: Learning to Surf, Mary Brady expertly guides the reader through the challenging and vital process of working with young analysands. Brady likens the experience to 'learning to surf.' While finding Bion's metaphor that the analyst must be able to 'think under fire' useful, she suggests 'learning to surf' is more apt in psychoanalysis with adolescents and children. Drawing on this metaphor throughout the volume, she describes how the adolescent can be potentially upended, injured or even killed by emotional waves too tumultuous to manage. Surfing also evokes the often uneasy, but sometimes thrilling balances of adolescence. Using clinical vignettes from her extensive experience in the field, Brady explores how to work with young people experiencing issues such as eating disorders, gender challenges, parental substance abuse and the impact of the COVID-19 pandemic. Drawing on Bionian Field Theory, as well as the work of Donald Winnicott, she explores how analysts can surf with the adolescent or child in navigating the ebb and flow of psychic life and development. This book is essential reading for psychoanalysts and psychotherapists, including psychiatrists, psychologists, therapists and counsellors, who treat children and adolescents"--
Keywords: Adolescent psychiatry; Child psychiatry